Unfreedom of the press [compact disc, unabridged] - Levin, Mark R. (Mark Reed), 1957- (Simon & Schuster, 2019)
FOX News star, and radio host Mark R. Levin delivers groundbreaking and enlightening book that shows how the great tradition of the American free press has degenerated into a standardless profession that has squandered the faith and trust of the American public, not through actions of government officials, but through its own abandonment of reportorial integrity and objective journalism.